INTERFERENSI BAHASA MELAYU MALAYSIA TERHADAP BAHASA INDONESIA PADA MASYARAKAT TKI KECAMATAN SIKUR - Muh. Jaelani Al-Pansori (MABASAN, 2014)
It is a common phenomenon that many rural populations work in Malaysia well known as Indonesian Labors (TKI). Even, some of them have been working for 5 years without passport. Their long period serving as Malaysian TKI affects to the ungrammatical and interference usage of Indonesian language. This study focuses on the causes and interferences form of Malayan language towards the TKI’s Indonesian language performance in Sub-district of Sikur. This is descriptive and qualitative study. The data is collected by using recording and interview technique. Then, the recording data is transcribed into written form and is analyzed by using interactive analysis with the following steps: data collection, data reduction, data display, and conclusion. Based on the data analysis, it is concluded that the interferences occurred among the Malaysian TKI populations are caused by interaction, habitual use of Malayan language for communication and their long period serving as TKI. In addition, forms of language interferences of the Malaysian TKI are phonological interference which occurs through shift of vowel phoneme, shift of consonant phoneme, and articulation of vowel and consonant phoneme. Beside that, morphological interference also occurs through prefix di-, clitics –nya, preposition di, full reduplication and partial reduplication. Finally, syntactic interference occurs in term of function, category and role.